2009
DOI: 10.1177/1470320309104873
|View full text |Cite
|
Sign up to set email alerts
|

Lack of genetic association between the angiotensin-converting enzyme gene insertion/deletion polymorphism and longevity in a Han Chinese population

Abstract: Introduction. The insertion/deletion polymorphism of the angiotensin-converting enzyme (ACE) gene has been reported to associate with human longevity. However, little information is available in a Han Chinese longevity population. Therefore, we investigated the association of the ACE gene insertion/ deletion polymorphism with longevity in a Han Chinese population. Materials and methods. We compared the distribution of ACE insertion/deletion genotype and allele frequencies in two groups: a longevity group (399 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 22 publications
3
18
0
Order By: Relevance
“…On the other hand, our study has some strengths. Similarly to other studies in this area, 16 we performed a second PCR to avoid a misclassification of ID heterozygotes as DD homozygotes. With regards to this, re-genotyping in 2001 of the samples from the pioneer study showing higher frequency of the D allele in French centenarians 6 revealed a 5% difference with the original data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, our study has some strengths. Similarly to other studies in this area, 16 we performed a second PCR to avoid a misclassification of ID heterozygotes as DD homozygotes. With regards to this, re-genotyping in 2001 of the samples from the pioneer study showing higher frequency of the D allele in French centenarians 6 revealed a 5% difference with the original data.…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between the D allele and increased longevity has not been replicated in other studies on centenarians from Denmark, 11 France, 12 Italy, 13,14 Korea 15 or China (Han population). 16 To further complicate the issue, Forero et al 17 recently reported an age-related decrease of the D allele in a Latin-American population (Colombia). Controversy between studies can arise from different factors, including homogeneity of cohorts within a given report or geographic differences between studies.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, other authors [71] found that the frequency rate of the D allele in the group of centenarians was significantly higher than that of the group aged 65-70 years, and the frequency rates of genotype DD were significantly higher in the centenarian group than in the controls. Yang et al [72] reported no association of the ACE gene polymorphism with longevity in Han Chinese individuals aged over 90 years. Also, Nacmias et al [73] did not find any involvement of the D allele in longevity.…”
Section: Angiotensin-converting Enzymementioning
confidence: 99%
“…These studies include rs2542052 in APOC3 (Novelli et al 2008), rs5882 in CETP (Cellini et al 2005;Novelli et al 2008), I/D insertion/deletion in ACE (Agerholm-Larsen et al 1997;Bladbjerg et al 1999;Blanche et al 2001;Yang et al 2009), rs1800562 in HFE (Carru et al 2003;Coppin et al 2003), and rs180113 in MTHFR (Bladbjerg et al 1999;Khabour et al 2009;Hessner et al 2001;Brattstrom et al 1998) and−176C/G in IL6 (Pes et al 2004;Wang et al 2001). Furthermore, a few meta-analyses or pooled analyses have been published; for APOE Δ4 and the ACE I/D, insertion/deletion association was supported (McKay et al 2011;Zajc et al 2012), while for the IL6 −176C/G polymorphism, a North/South European gradient of association was suggested (Di Bona et al 2009).…”
Section: Introductionmentioning
confidence: 99%